2016
DOI: 10.1590/1519-6984.18514
|View full text |Cite
|
Sign up to set email alerts
|

Fish hatchering and its effects on the morphology of Prochilodus lineatus (Actinopterygii: Prochilodontidae)

Abstract: The fish stocking in captivity for later release into natural water bodies has historically been applied in Brazil, as a measure to mitigate impacts caused by dams. However, the released fish are adapted to the hatchery environment, which is totally different from the natural, which results in low post-release survival rates and ineffectiveness of stocking as a management measure. Worldwide, several studies have demonstrated the existence of large phenotypic differences between farmed and wild fish, but in Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 29 publications
(50 reference statements)
0
15
1
Order By: Relevance
“…On the contrary, social enrichment seems to have diluted the effect of structural enrichment, as structuring ceased to be as important for curimba morphological variation when in the presence of piapara. One of the most important results of this study, it was that the social enrichment had increased the morphological variability in the reared curimba populations, approaching them of the wild populations (Taylor, 1986;Saraiva and Pompeu, 2016).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…On the contrary, social enrichment seems to have diluted the effect of structural enrichment, as structuring ceased to be as important for curimba morphological variation when in the presence of piapara. One of the most important results of this study, it was that the social enrichment had increased the morphological variability in the reared curimba populations, approaching them of the wild populations (Taylor, 1986;Saraiva and Pompeu, 2016).…”
Section: Discussionmentioning
confidence: 67%
“…Wild populations exhibit great variability in shape (Taylor, 1986;Saraiva and Pompeu, 2016). Therefore, simply using two or more species is a potential management tool in hatcheries to obtain fish more similar to wild ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, training fish to recognize predators by exposing them to predator cues can increase antipredator behavior (Becker & Gabor, 2012; Crane et al, 2015; Keefe, 1992; but see Kopack et al, 2023), and fish can learn to associate a visual cue, like a model of a predator, with danger when paired with conspecific alarm cue or an identifying predator odor (Becker & Gabor, 2012; Brown & Laland, 2001; Olla et al, 1998; Vilhunen, 2006). Similarly, abiotic enrichment to make the captive environment more natural shows promise for increasing expression of phenotypes associated with surviving predator encounters after release (Belk et al, 2008; Chittenden et al, 2010; Fuss & Byrne, 2002; Hutchison et al, 2012; Saraiva & Pompeu, 2016; Ullah et al, 2017). Subjecting hatchery‐reared fish to variable temperatures, variable flow, and/or structure (e.g., artificial plants and refugia) can shift traits like thermal tolerance (Blair & Glover, 2019), metabolic rate (Cook et al, 2018), muscle development (Evans et al, 2015), swimming performance (Bergendahl et al, 2017; Chittenden et al, 2010; Higham et al, 2015), personality (Brignon et al, 2018; Lee & Berejikian, 2008), neural plasticity (Salvanes et al, 2013), and stress levels (Zhang et al, 2020) to more closely match those observed in wild fish.…”
Section: Introductionmentioning
confidence: 99%
“…Ecological morphology, or ecomorphology, is the branch of ecology that studies the relationships between morphology and ecological aspects among individuals, populations, guilds, and communities (Karr and James 1975, Gatz 1979b, Winemiller 1992, Chapman et al 2015. For a long time, ecologists have been interested in the relationship between the morphology of organisms, their ecological performance and the evolutionary consequences of this relationship for the selection and maintenances of adaptative traits in populations (Gatz 1979a, Wikramanayake 1990, Winemiller 1991, Leal et al 2011, Saraiva and Pompeu 2016. Ecomorphological studies of fish aim to understand the importance of certain attributes in the ecology of the species and how they influence their adaptation to different habitats (Douglas and Matthews 1992, Norton et al 1995, Casatti and Castro 2006, Lailvaux and Husak 2014.…”
Section: Introductionmentioning
confidence: 99%